MR properties of 19F C3F8 gas in the lungs of healthy volunteers: T2∗ and apparent diffusion coefficient at 1.5T and T2∗ at 3T. Issue 3 (14th September 2020) - Maunder, Adam; Chan, Ho‐Fung; Hughes, Paul J. C.; Collier, Guillhem; Norquay, Graham; Rodgers, Oliver; Thelwall, Peter; Robb, Fraser; Rao, Madhwesha; Wild, Jim M.
Abstract : Purpose: To measure the transverse relaxation time ( T 2 ∗ ) and apparent diffusion coefficient (ADC) of 19 F‐C3 F8 gas in vivo in human lungs at 1.5T and 3T, and to determine the representative distribution of values of these parameters in a cohort of healthy volunteers. Methods: Mapping of ADC at lung inflation levels of functional residual capacity (FRC) and total lung capacity (TLC) was performed with inhaled 19 F‐C3 F8 (eight subjects) and 129 Xe (six subjects) at 1.5T. T 2 ∗ mapping with 19 F‐C3 F8 was performed at 1.5T (at FRC and TLC) for 8 subjects and at 3T (at TLC for seven subjects). Results: At both FRC and TLC, the 19 F‐C3 F8 ADC was smaller than the free diffusion coefficient demonstrating airway microstructural diffusion restriction. From FRC to TLC, the mean ADC significantly increased from 1.56 mm 2 /s to 1.83 mm 2 /s ( P = .0017) for 19 F‐C3 F8, and from 2.49 mm 2 /s to 3.38 mm 2 /s ( P = .0015) for 129 Xe. The posterior‐to‐anterior gradient in ADC for FRC versus TLC in the superior half of the lungs was measured as 0.0308 mm 2 /s per cm versus 0.0168 mm 2 /s per cm for 19 F‐C3 F8 and 0.0871 mm 2 /s per cm versus 0.0326 mm 2 /s per cm for 129 Xe. A consistent distribution of 19 F‐C3 F8 T 2 ∗ values was observed in the lungs, with low values observed near the diaphragm and large pulmonary vessels. The mean T 2 ∗ across volunteers was 4.48 ms at FRC and 5.33 ms at TLC for 1.5T, and 3.78 ms at TLC for 3T. Conclusion: In this feasibility study, values of physiologically relevant parameters of lung microstructure measurable by MRI ( T 2 ∗, and ADC) were established for C3 F8 in vivo lung imaging in healthy volunteers.